Libraries@75 : journey of libraries towards knowledge resource centers - Sangeeta Dhamdhere-Rao; Sanjay Sopan Kharat (Ess Ess, New Delhi, 2023)
This book gives an overview of an evolutionary journey of all types of libraries in India post and pre Independence. The journey of libraries after independence is a reflection of the hard work, innovation, technology and development. Whether in India or abroad, library professionals have proved themselves with their research, innovative ideas and their implementation. The book contains information about public libraries, school, academic as well as research libraries in India and discusses infrastructure, collection developments and technological transformation in these libraries. It also covers library movement, library legislation, LIS education, education policies and academic library initiatives during Ancient India, Medieval India, Pre and Post Independence of India by the Government. It also discusses professional librarian skills based on library science functional laws and how their roles transformed in the last 75 years to provide better information services. This historic document in the form of a book on Indian Libraries and their journey in the last 75 years is being presented on the occasion of Azadi Ka Amrut Mahotsav. About the Author Dr. Sangeeta Dhamdhere-Rao is a Library Professional from India and has 20 years of experience as an Academic Librarian. He has completed her Masters in Library and Information Science from Savitribai Phule Pune University and Ph.D. from RTM Nagpur University. She has published more than 63 research publications which includes 45 research papers, 7 books and 11 chapters. She is recipient of VLIR fellowship of Flemish Inter-University Council, Belgium and has completed three research projects funded by her parent University and Antwerp University, Belgium. She has travelled to many countries like the USA (Harvard University, New York University, University of Washington, MIT, and Library of Congress), Europe (Antwerp, Vrije and Ghent Universities), Japan (National Institute of Informatics, Tokyo, and Sapporo), China .
Includes bibliographical references.
Keywords: Library Science